Comparative Analysis of Lower Limb Alignments in Healthy Subjects and Subjects with Back Pain - Ramin Balouchy (The Society of Aging and Physical Activity (SAPA), 2015)
The objective of the present study was to comparatively analyze the clinical status of the lower limbs in healthy subjects and subjects with back pain. Forty three (43) male and female subjects with average age of 36.91± 3.97 were selected as the statistical sample of the study. This population was recognized intelligently by utilizing the Nordic Musculoskeletal Questionnaire (NMQ). Furthermore, the NMQ was used to designate 43 male and female subjects with average age of 37.88 ± 4.12 and similar anthropometric characteristics with the statistical population as the research control sample. In the next phase, tibial torsion and femoral torsion angles were measured using a goniometer. Foot typicality was designated using a foot arch index while intercondylar and intermalleolar distances were measured using a clinical caliper. The results depict that the size of the foot arch is steeper in people with back pains compared to those with flat foot arch (p<0.05). It also indicates that there is no significant correlation between the tibia, femur torsion, knee condition of the healthy subjects and subjects with back pain. Therefore, it is deduced that steep foot arch can be a key component in the generation of back pains.